Low prenatal resting energy expenditure and high energy intake predict high gestational weight gain in pregnant women with overweight/obesity. Issue 4 (July 2022) - Leonard, Krista S.; Symons Downs, Danielle
Abstract: Introduction: Recent evidence suggests that low resting energy expenditure (REE) is associated with gestational weight gain (GWG). However, little research has examined whether REE explains GWG beyond the contributions of energy intake (EI) and physical activity (PA). This study examined the extent to which EI, PA, and REE were associated with and explained second trimester GWG in pregnant women with overweight/obesity. Methods: Pregnant women with overweight/obesity ( N  = 26) participating in the Healthy Mom Zone study, a theoretically-based behavioral intervention that adapted the intervention dosage over time to regulate GWG completed weekly point estimates of EI (back-calculation), PA (wrist-worn activity monitor), and REE (mobile metabolism device) from 14- to 28-weeks gestation. Second trimester GWG was calculated as the weekly point estimate of weight from a Wi-Fi weight scale at gestational week 28 minus the weekly point estimate of weight at gestational week 14. Results: Partial correlations revealed second trimester EI and PA were not significantly associated with second trimester GWG, but low second trimester REE was significantly associated with high second trimester GWG. Hierarchical regression analyses showed the model of fat-free mass, EI, PA, and REE explained 56% of the variance in second trimester GWG. Low REE was the strongest determinant followed by high EI; fat-free mass and PA were not significant predictors. Conclusions: While EI and PA remain important determinants of GWG, future researchers should explore the role of REE to inform individualized EI and PA goals to better regulate GWG. Highlights: This study examined prenatal resting energy expenditure (REE) as a predictor of gestational weight gain. Low REE and high energy intake predicted second trimester gestational weight gain. Future researchers should explore the role of REE for prenatal weight gain interventions.